2002
DOI: 10.1292/jvms.64.107
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Estradiol-3-Benzoate Down-Regulates the Expression of Testicular Steroidogenic Enzyme Genes for Testosterone Production in the Adult Rat.

Abstract: ABSTRACT. To study the role of estrogen in the testes, testosterone and testicular steroidogenic enzyme mRNA levels were investigated in male Sprague-Dawley rats 24 hr after intramuscular administration of a single dose of estradiol-3-benzoate (EB). EB administration resulted in a greater decrease in intra-testicular and serum testosterone in 10-week-old rats than in 3-or 5-week-old rats. A dose of 2 µg EB/kg had the lowest observed effect. The level of serum luteinizing hormone (LH) was unchanged at any dose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…However, another possible explanation for our finding is that estradiol suppresses testicular CYP1B1 expression by a mechanism independent of LH. This proposal is consistent with the observation that administration of exogenous estradiol to intact adult rats leads to decreased testicular mRNA levels of steroidogenic enzymes, especially CYP17A1 and CYP11A1, but this occurs without altering serum LH levels (Sakaue et al, 2002).…”
Section: Leung Et Alsupporting
confidence: 91%
“…However, another possible explanation for our finding is that estradiol suppresses testicular CYP1B1 expression by a mechanism independent of LH. This proposal is consistent with the observation that administration of exogenous estradiol to intact adult rats leads to decreased testicular mRNA levels of steroidogenic enzymes, especially CYP17A1 and CYP11A1, but this occurs without altering serum LH levels (Sakaue et al, 2002).…”
Section: Leung Et Alsupporting
confidence: 91%
“…Steroidogenic enzymes responsible for production of androgens are known to be regulated by E 2 (Sakaue et al 2002) and a decrease in testosterone levels is commonly observed with E 2 and DES administration Goyal et al 2001). The serum testosterone levels at higher doses of PPT were reduced to 25% of the control values (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The primers used for RT-PCR for StAR protein and cytochrome P 450 scc were gene-specific primers selected according to Akingbemi et al (2004). The 3b-HSD type I and 17b-HSD type III were selected according to Sakaue et al (2002).Ten microliters of each PCR product were analyzed by gel electrophoresis on a 2% agarose gel. The molecular size of the amplified products (StAR, P450scc, 3b-HSD, 17b-HSD, and RPS 16) was determined by comparison with molecular weight marker (100 bp DNA ladder) run in parallel with RT-PCR products.…”
Section: Rt-pcrmentioning
confidence: 99%